Penentuan Rekomendasi Laptop Terbaik Bagi Customer Dalam Sistem Pendukung Keputusan Dengan Metode SAW Di CV. Jeflin Laptop - Evaristus Nardo; Asrul Sani; Agusta Pratama Wibawa; Nur Nawaningtyas Pusparini (Pusat Riset dan Inovasi Nasional, 2024)
A laptop device is a technology in portable form that can be used to process data like a computer, making it easier for every job in its respective field that uses the system. The aim of the research carried out is to analyze customer needs for the desired laptop and determine the choice of the best laptop, the solution used is the SAW method for selecting the best laptop, then the results obtained from the SAW method process have conceptual stages, namely, determining SAW criteria, determining variable benefit and cost criteria, determining the weight of each criterion, determining SAW alternatives, normalizing the matrix, calculating the V value and ranking based on laptop brands such as Acer, Lenovo, Asus, HP, Dell and MSI.